Experimental study of fluid phase equilibrium along thermodynamically optimized interface of a stored liquid container - Rakshit, D.; Narayanaswamy, Ramesh; Thiagarajan, K. (The American Society of Mechanical Engineers, 2016)
© 2016 by ASME. This experimental study presents the thermal optimization of a storage container partially filled with liquid (water) with an ullage region above the liquid composed of water vapor and air. The basic purpose of this thermal optimization was to qualitatively explore the design conditions that minimize the heat leaks from the storage tank to the external environment at a lower temperature than the liquid in the storage container. Two symbiotic physical parameters-interfacial mass transfer and the entropy generated by the system-influence the thermal performance of the storage container. These two symbiotic physical parameters were simultaneously considered when optimizing the system. The mass transfer estimation involved the determination of (i) the liquid-vapor interfacial temperature, (ii) the fractional concentration of the evaporating liquid present in the gaseous state, and (iii) the surface area of the liquid-vapor interface. The entropy of the system was estimated separately by considering the entropy of the diabatic saturated liquid and the ullage vapor. A synergistic objective function was subsequently composed based on the penalty involved in deviation from the individual optima, thus determining a holistic optimum. The results show that stored liquids exhibit better second-law efficiency in open containers than in containers that are closed by a lid. The primary factor that influences this optimum is the lid condensation that occurs in closed containers at the 50% filling level.